2024
DOI: 10.1002/mrc.5438
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complex mixtures with benchtop nuclear magnetic resonance: Solvent suppression with T2 and diffusion filters

Anh Le‐McClain,
Curt Zanelotti,
Hector Robert
et al.

Abstract: Benchtop nuclear magnetic resonance (NMR) spectrometers are being employed in a wide variety of applications from undergraduate teaching and research in academia to quality control and process monitoring in industrial settings. Incorporating benchtop NMR in some of these applications presents opportunities for new practical uses of the technology and challenges that truly test the capabilities of compact NMR spectrometers. For instance, the use of protonated solvents in manufacturing or process monitoring requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Extension of PS80 quantification in HPV VLP vaccine to low-field has recently been suggested by Rustandi . Additionally, while this manuscript was undergoing peer review, a study by Le-McClain et al (independent of the work reported here) demonstrated the application of T 2 and diffusion filters with WET water suppression for the quantification of P188 in formulated bovine serum albumin (BSA) solutions …”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Extension of PS80 quantification in HPV VLP vaccine to low-field has recently been suggested by Rustandi . Additionally, while this manuscript was undergoing peer review, a study by Le-McClain et al (independent of the work reported here) demonstrated the application of T 2 and diffusion filters with WET water suppression for the quantification of P188 in formulated bovine serum albumin (BSA) solutions …”
Section: Introductionmentioning
confidence: 78%
“…18 Additionally, while this manuscript was undergoing peer review, a study by Le-McClain et al (independent of the work reported here) demonstrated the application of T 2 and diffusion filters with WET water suppression for the quantification of P188 in formulated bovine serum albumin (BSA) solutions. 31 In this study, we demonstrate that benchtop NMR spectroscopy is a greener alternative to common LC-based methods suitable for the routine quantification of NISE under conditions relevant to the biopharmaceutical industry. We first consider the need for a rapid method to verify quantitatively that surfactant stock solutions used in biopharmaceutical manufacturing are accurately prepared.…”
Section: ■ Introductionmentioning
confidence: 79%